External Quality Assessment/Proficiency Testing and Internal Quality Control for the PFA-100 and PFA-200: An Update - Favaloro, Emmanuel J.; Bonar, Roslyn (Seminars in Thrombosis and Hemostasis, 2014)
Platelet function testing is an essential component of comprehensive hemostasis evaluation within the framework of bleeding and/or bruising investigations, and it may also be performed to evaluate antiplatelet medication effects. Globally, the platelet function analyzer (PFA)-100 (Siemens Healthcare, Marburg, Germany) is the most used primary hemostasis-screening instrument and has also been recently remodeled/upgraded to the PFA-200. The PFA-100 is sensitive to a wide range of associated disorders, including platelet function defects and von Willebrand disease (VWD), as well as to various antiplatelet medications. The PFA-100 is also useful in therapy monitoring, especially in VWD. External quality assessment (EQA) (or proficiency testing) and internal quality control (IQC) are critical to ensuring quality of test practice, inclusive of all hemostasis tests. However, both EQA and IQC for platelet function testing, including the PFA-100, is logistically challenging, given theoretical requirements for production, storage, and shipment of large volumes of “stabilized” normal and pathological blood/platelets covering both normal function plus a wide variety of potential defects. We accordingly describe the development and testing of novel feasible approaches to both EQA and IQC of PFA-100/PFA-200 instruments, whereby a range of formulated “platelet function antagonist” materials are utilized. For EQA purposes, these are distributed to participants, and citrated normal whole blood collected on site is then added locally, thereby creating test material that can be locally evaluated. Several exercises have been conducted by the Royal College of Pathologists of Australasia Quality Assurance Program (RCPAQAP) over the past 6 years. A total of 26 challenges, with most designed to mimic moderate to severe primary hemostasis defects, have been tested in 26 to 50 laboratories depending on the year of dispatch. Numerical results for PFA-100/PFA-200 closure times (CTs) and interpretive comments supplied by participants are analyzed by the RCPAQAP. During this period, reported CTs for each challenge were within limits of expectation and good reproducibility was evidenced by repeated challenges. Coefficients of variation (CVs) generated for challenges using the two major PFA-100/PFA-200 cartridge types (collagen/adenosine diphosphate and collagen/epinephrine) are always similar to those obtained using native whole blood, and in general range from 15 to 25%. Interpretations are also in general consistent with expectations and test data provided by laboratories. The EQA created material has also been assessed within the context of possible IQC material. In conclusion, EQA and IQC processes for the PFA-100/PFA-200 have been developed that include highly reproducible test challenge processes, not only supporting the concept that EQA/IQC is possible for platelet function testing but also providing a valuable mechanism for monitoring and improving laboratory performance in this area.
Keywords: PFA-100; PFA-200; platelet function analyzer; external quality assessment; proficiency testing; quality control; IQC; EQA